Reissuable Biometrics Through Offline Handwritten Signature Verification - Ooi, Shih Yin (2008)
In this thesis, an ffline handwritten verification system is proposed. The system canbe viewed in image acquisition and preprocessing module, enrolment and verification modules. Image acquisition and preprocessing module is responsible for extracting signature image from a scanned document and fterwards preprocessing it for farther feature extraction.